Market response to investor sentiment - Jördis Hengelbrock; Erik Theissen; Christian Westheide (Goethe University Frankfurt, Center for Financial Studies (CFS), 2011)
This paper reconsiders the effect of investor sentiment on stock prices. Using survey-based sentiment indicators from Germany and the US we confirm previous findings of predictability at intermediate time horizons. The main contribution of our paper is that we also analyze the immediate price reaction to the publication of sentiment indicators. We find that the sign of the immediate price reaction is the same as that of the predictability at intermediate time horizons. This is consistent with sentiment being related to mispricing but is inconsistent with the alternative explanation that sentiment indicators provide information about future expected returns.
urn:nbn:de:hebis:30-91456
Keywords: G12; G14; 330; Investor Sentiment; Event Study; Return Predictability; Börsenkurs; Kapitalertrag; Prognoseverfahren; Anlageverhalten; Meinung; Deutschland; USA